Exploring online identity construction for the caregivers of adults living with dementia and the value of interactions with health and social care professionals. (24th April 2021) - Prato, Laura; Abley, Clare; Adamson, Joy
Abstract: Becoming an informal caregiver for an adult living with dementia has been shown to have a significant impact upon the conception of identity. This study aimed to identify how identity is constructed online amongst caregivers of individuals living with dementia and how healthcare interactions can influence identity development through the analysis of online web blogs. Sixteen online blogs (172 entries) were selected through purposive and snowball sampling, and discourse analysis was used to analyse online identity construction for informal caregivers of adults living with dementia. Six areas of online identity construction were identified: changing family role; powerful expert social campaigner; being an advocate; guardian of their relative's selfhood; sustaining creative and spiritual individuality and wider community member in online and real life. Further to this, the importance of health and social care service interactions in the development of caregiver identity revealed that professionals must ensure person‐centred service contacts for caregivers. This is a challenging task in the pandemic climate where interactions between health and social care professionals and caregivers are limited due to isolation measures. It is evident that the blog format can provide a forum through which the identity of the caregiver of an adult living with dementia can evolve. The six areas of identity construction reveal the multifaceted nature of identity for the caregiver and the value of belonging to an online community both in relation to identity construction and support. This finding is especially applicable in the current pandemic when accessing a face‐to‐face community is challenging for caregivers who may be shielding or living in isolation. The findings of this research can aid health and social care professionals in understanding the development of caregiver identity and in providing appropriate support during service interactions, on accessing virtual and face to face community support.